SELECTED SCHOOL BASED FACTORS' INFLUENCE ON VALUE ADDITION IN SECONDARY EDUCATION IN PUBLIC SECONDARY SCHOOLS IN RACHUONYO SOUTH SUB-COUNTY, KENYA - Odera, Odera; Sika, James; Olel, Maureen (African Journal of Education and Practice, 2022)
Purpose: The study sought to determine value addition in secondary education of 2013 and 2014 cohorts in public secondary schools in Rachuonyo South Sub-county and to examine selected school based factors' influence on value addition in secondary education. Methodology: The study adopted a correlational design. Correlational research design was appropriate for this study since it enabled the researcher to collect independent and dependent variable data sets with a view to determine the relationship between them (Creswell, 2012). The population comprised 49 public secondary schools in Rachuonyo South Sub-County, 49 Deputy Principals and 5132 students. The researcher used Yamane's formula to compute a sample of 39 public secondary schools, from where 39 Deputy Principals and 4351 students were purposively sampled. Data were collected using document analysis guide and questionnaires and analysed using frequencies, means and regression analysis with the aid of SPSS V.25 software. Findings: Findings revealed value additions of -1.563125 for 2013 cohort. Regression analysis revealed that performance appraisal accounts for 17% change in value addition in secondary education of the 2013 cohort and that teachers' professional development (Î²=0.325, p=0.040) has a weak significant positive relationship with value addition in secondary education of 2013 cohort. For the 2014 cohort, findings revealed value addition of -1.9363125. Regression analysis revealed that teachers' performance appraisal account for 12% change in value addition in secondary education and that teachers' performance appraisal (Î²=0.386, p=0.009) has a weak significant positive relationship with value addition in secondary education. Unique contribution to model and practice: The study contributes to literature by providing analysis of value addition in secondary education and teacher performance appraisal contribution to value addition in the context of Kenya.